Norwegian Bay, quadrangle, Minnesota - St. Louis Co. 7.5 minute series (topographic) - Minnesota. Department of Conservation (Washington, D.C. : Geological Survey (U.S.), 1986)
Relief shown by contours. Color; 1:24,000